A common language*. Issue 1 (2nd January 2017) - Weber, Marc
ABSTRACT: Both the Internet and the Web beat out numerous rivals to become today's dominant network and online system, 1 respectively. Many of those rival systems and networks had developed alternative solutions to issues that face us today, from micropayments to copyright. But few scholars, much less thought leaders, have a meaningful overview of the origins of our online world, or of the many systems which came before. This exclusivity is a problem, since as a society we are now making some of the permanent decisions that will determine how we deal with information for decades and even centuries to come. Those decisions are about regulatory structures, economic models, civil liberties, publishing and more. This essay argues for the need to comparatively study online information systems across all these axes, and to thus develop a "common language" of known precedents and concepts as a prerequisite for making informed discussions about the future of the online world. Doing so depends on two factors: (1) preservation of enough historical materials about earlier systems to be able to meaningfully examine them; (2) interdisciplinary, international attention to "meta" stories that emerge from considering the evolution of multiple networks and online systems.